Leveraging bio-based monomers, chemical recyclability, and sustainable polymerization techniques for sustainable polymer synthesis - Bernsten, Simone Noelle, author; Miyake, Garret, advisor; McNally, Andy, committee member; Reynolds, Melissa, committee member; Reisfeld, Brad, committee member (Colorado State University. Libraries, 2024)
Polymeric materials have become vital to everyday life since their commercialization. Although polymers are integral to many industries and consumers, their synthesis and use brings with them a myriad of environmental concerns. Unsustainability can arise even before polymer synthesis in that many synthetic polymers are made from petroleum-derived monomers which are inherently nonrenewable. Next, many polymers are synthesized using one or more unsustainable components such as precious metals including iridium and ruthenium. Finally, at the end of a polymer's useful life, options for recycling are limited by the inability to make virgin-quality materials that can be used for the same application as the original polymer. The work described in this thesis aims to address each of these issues. The polymerizations of several bio-based monomers are described. The use of organic photoredox catalysis to enable polymerization represents sustainable synthesis of polymers. Polymers exhibiting chemical recyclability are also investigated, wherein end-of-life materials can be depolymerized and used to produce virgin- quality materials. Ultimately, this work represents a diverse array of methodologies for increasing the overall sustainability of polymeric materials.